MUTU PENDIDIKAN ISLAM DALAM PERSPEKTIF AL-QURAN DAN TAFSIR - rahmita maulina mayang; Ibnu Rawandhy N. Hula; Mariaty Podungge; Wahyu Mokodongan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2023)
The goal of this study is to find out how the Koran and its interpretation describe the quality of Islamic education. The literature review incorporates the conducted search. This qualitative research is part of the kind of library research that uses analytical and descriptive methods. The qualitative descriptive method was analyzed in this study using a variety of approaches. The first step in this study is to examine everything in the Koran that ensures Islamic education quality. Second, examine all of the Hadith, Koran, and other verses that are comparable to education. Thirdly, investigate the verses of the Koran, the Hadith that describes the Prophet Muhammad SAW's daily activities, and the components of the quality of education. The fourth step is concentrating on science, which can be as an essential hypothesis or idea with respect to the nature of Islamic instruction from the stanzas of the Qur'an and hadith, or regular occasions. Fifth, make inferences based on the analysis's findings. The qualitative textual data used in this study combines primary, secondary, and complementary data. the kind of education that is well-liked by the community as well as schools, as well as the kind of education that can assist students in developing relative reasoning. Schools and quality are working to foster an environment where learning the Koran and its translation can be used as an educational experience, particularly in granting the best wishes.